Fabrication of Low-Power Consumption Hydrogen Sensor Based on TiOx/Pt Nanocontacts via Local Atom Migration - Yasuhisa Naitoh; Hisashi Shima; Hiroyuki Akinaga (Nanomaterials)
Hydrogen (H2) gas sensors are essential for detecting leaks and ensuring safety, thereby supporting the broader adoption of hydrogen energy. The performance of H2 sensors has been shown to be improved by the incorporation of TiO2 nanostructures. The key findings are summarized as follows: (1) Resistive random-access memory (ReRAM) technology was used to fabricate extremely compact H2 sensors via various forming techniques, and substantial sensor performance enhancement was investigated. (2) A nanocontact composed of titanium oxide (TiOx)/platinum (Pt) was subjected to various forming operations to establish a Schottky junction with a nanogap structure on a tantalum oxide (Ta2O5) layer, and its properties were assessed. (3) When the Pt electrode was on the positive side during the forming operation used for ReRAM technology, a Pt nanopillar structure was produced. By contrast, when the forming operation was conducted with a positive bias on the TiOx side, a mixed oxide film of Ta and Ti was produced, which indicates local Ta doping into the TiOx. A sensor response of over 1000 times was achieved at a minimal voltage of 1 mV at room temperature. (4) This sensor fabrication technology based on the forming operation is promising for the development of low-power consumption sensors.